Delay to surgery in acute perforated and ischaemic gastrointestinal pathology: a systematic review. Issue 5 (3rd September 2021) - Murray, V; Burke, J R; Hughes, M; Schofield, C; Young, A
Abstract: Background: Patients with acute abdominal pathology requiring emergency laparotomy who experience a delay to theatre have an increased risk of morbidity, mortality and complications. The timeline between symptom onset and operation is ill defined with international variance in assessment and management. This systematic review aims to define where delays to surgery occur and assess the evidence for interventions trialled across Europe. Methods: A systematic review was performed searching MEDLINE and EMBASE databases (1 January 2005 to 6 May 2020). All studies assessing the impact of time to theatre in patients with acute abdominal pathology requiring emergency laparotomy were considered. Results: Sixteen papers, involving 50 653 patients, were included in the analysis. Fifteen unique timepoints were identified in the patient pathway between symptom onset and operation which are classified into four distinct phases. Time from admission to theatre (1–72 hours) and mortality rate (10.6–74.5 per cent) varied greatly between studies. Mean time to surgery was significantly higher in deceased patients compared with that in survivors. Delays were related to imaging, diagnosis, decision making, theatre availability and staffing. Four of five interventional studies showed a reduced mortality rate following introduction of an acute laparotomy pathway. Conclusion: Given the heterogeneous nature of the patient population and pathologies, an assessment and management framework from onset of symptoms to operation is proposed. This could be incorporated into mortality prediction and audit tools and assist in the assessment of interventions. Abstract : Whilst delay to theatre in patients with acute abdominal pathology requiring emergency laparotomy is associated with an increased risk of mortality, there is wide variation in the definition and measurement of time delays prior to emergency surgery with few studies exploring interventions to reduce delays. An assessment and management framework from onset of symptoms to operation is proposed.